L’obligation de moyens en matière de responsabilité médicale - Deschamps, Pierre (Assurances)

(untitled) (HEC Montréal, 1991)
In this article, the author analyses the distinctions between the obligation of means and the obligation of results in the light of professional liability for the physician. Me Deschamps endeavours to demonstrate that the concept of the obligation of means is clear but its application remains ambiguous. It seemed to the author that the former obligation is not less intensive, strong or constrained than the latter.